2022
DOI: 10.1097/pai.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Cancer Stem Cell Markers in Patients With Salivary Gland Carcinomas

Abstract: Objectives: Cancer stem cells (CSCs) are a small group of cells resistant to therapy and play a major role in tumor progression, recurrence, and poor clinical outcomes of patients. This study aimed to evaluate the association of CSC markers with clinicopathologic features and survival in patients with salivary gland carcinomas (SGCs). Materials and Methods:The medical records of 48 patients affected by mucoepidermoid carcinoma (MEC) and 47 patients with adenoid cystic carcinoma (AdCC) were reviewed retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Cancer stem cells (CSCs) are a group of cells that demonstrate therapeutic resistance and are found to aid in tumour progression, recurrence, poor clinical outcomes and overall survival. A significant correlation between the expression of SOX 2 and mucoepidermoid carcinoma was observed when compared to other CSC markers [ 6 ]. Systematic review and meta-analysis on gastric cancers showed the association of CSC marker expression to be in correlation with clinicopathological parameters and survival outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are a group of cells that demonstrate therapeutic resistance and are found to aid in tumour progression, recurrence, poor clinical outcomes and overall survival. A significant correlation between the expression of SOX 2 and mucoepidermoid carcinoma was observed when compared to other CSC markers [ 6 ]. Systematic review and meta-analysis on gastric cancers showed the association of CSC marker expression to be in correlation with clinicopathological parameters and survival outcome.…”
Section: Introductionmentioning
confidence: 99%